Learning styles and academic achievement: a case of UiTM students / Norhafiza Hashim...[et al.] - Anual, Norazlan; Abd Karim, Zatul Himmah; Mohd Azmi, Nor Farhana (2014)
It is important to note that individual differences affect different academic achievements. Besides being different in abilities, students have specific learning styles that may influence academic achievements (J. Alireza, 2011). Each individual has his own learning style preferences based on his personality and ability. This study aims to identify the types of learning styles among university students. It also aims to identify the different types of learning styles based on gender and variety field of study. In addition, this study also aims to determine the relationship between student learning styles and their academic achievement and to look into their academic achievement based on students’ CGPA. A total of 266 final semester students from Faculty of Business Management, Faculty of Accountancy, and Faculty of Computer and Mathematical Sciences of Universiti Teknologi MARA (Perak) and Universiti Teknologi MARA Kedah, were randomly selected as sample of this study. The result of analyses of variance show that there is a statistically significant difference in the academic achievement of these students that correspond to the four learning styles. It was found and concluded that converging learning styles scored the highest percentage among the respondents towards their academic performance. There is a strong relationship between student learning style and academic performance. The result showed there was a significant difference between gender and academic performance.